2006
DOI: 10.2106/jbjs.e.01407
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mechanical Loading on Intervertebral Disc Metabolism In Vivo

Abstract: The overall goal of this work is to define more clearly which mechanical loading conditions are associated with accelerated disc degeneration. This article briefly reviews recent studies describing the effects of mechanical loading on the metabolism of intervertebral disc cells and defines hypothetical models that provide a framework for quantitative relationships between mechanical loading and disc-cell metabolism. Disc cells respond to mechanical loading in a manner that depends on loading magnitude, frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 117 publications
(91 citation statements)
references
References 8 publications
1
81
0
Order By: Relevance
“…The variation of properties (biomechanical, morphological and cellular) between regions within the disc itself is also an important factor to consider in choosing and designing the model. For example, the cell types vary with location, with those from the annulus differing not only in morphology but also in their metabolism, response to applied loads, etc., from the cells within the NP [57,70,125,150].…”
Section: Anatomical Variationsmentioning
confidence: 99%
“…The variation of properties (biomechanical, morphological and cellular) between regions within the disc itself is also an important factor to consider in choosing and designing the model. For example, the cell types vary with location, with those from the annulus differing not only in morphology but also in their metabolism, response to applied loads, etc., from the cells within the NP [57,70,125,150].…”
Section: Anatomical Variationsmentioning
confidence: 99%
“…These dissimilarities on the other hand are due to hormonal differences and the onset of menstruation-related pain in women [36]. Nevertheless, disc degeneration is multifaceted, traditionally attributed to age, mechanical loading, gender, trauma, obesity and other factors impairing disc nutrition [37][38][39][40][41].…”
Section: Bdimentioning
confidence: 99%
“…It is possible that the motion or change in stress results in mechanobiological events that lead to pain relief or promote disc health [39,40]. Studies using both animal and in vitro models have demonstrated that mechanical stress may play a role in the regulation of both degradative and anabolic processes in discs [41][42][43].…”
Section: Discussionmentioning
confidence: 99%